Tilt detection of connectors using phase shifting - Retnasamy, V.; Mani Maran, Ratnam; Sundaraj, Kenneth; Zaliman, Sauli (International Association of Science and Technology for Development (IASTED)/ACTA Press, 2009)
Link to publisher's homepage at http://www.iasted.org/